Long-term prognosis of geriatric major depression in relation to cognition and white matter integrity: follow up of two cases - Alves,Carlos Eduardo de Oliveira (2012)
INTRODUCTION: The geriatric depression (GD) represents one of the most frequent psychiatric disorders in outpatient services specialized in old-age treatment. OBJECTIVE: The course of two illustrative cases of GD is discussed, highlighting its clinical picture after antidepressant treatment and underlining variables related to disease prognosis, treatment effectiveness and conversion to major cognitive disorders such as vascular dementia (VD). METHODS: The cognitive performance, depressive symptoms, autonomy and brain structural measurements as white matter hyperintensities (WMH) and hippocampal size, and microstructural integrity of WM with diffusion tensor imaging were followed during four years. RESULTS: Case 1, with a severe degree of WMH, was associated with worsening cognition and increasing functional disability. Case 2, with mild WMH, an improvement of cognitive functioning could be seen. CONCLUSIONS: The existence of different subtypes of GD, as presented in this report, points a pathophysiological heterogeneity of GD, and suggests a possible continuum vascular depression (VaDp) and vascular cognitive impairment (VCI).